2013
DOI: 10.1007/s11999-013-3069-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Premorbid Glenoid Anatomy Altered in Patients with Glenohumeral Osteoarthritis?

Abstract: The glenoid vault model may be a clinically useful tool to estimate patient-specific premorbid glenoid anatomy, which may help in preoperative or intraoperative surgical planning for total shoulder arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…The finding of glenoid inferior inclination on the impaired side is a novel result for the study of children affected by OBPP and is supported by a similar finding in a recent rat study . Studies focused on adult shoulder pathology have frequently evaluated both glenoid version and inclination . One of the key findings of these studies is that superior glenoid inclination increases the risk of superior humeral head translation .…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The finding of glenoid inferior inclination on the impaired side is a novel result for the study of children affected by OBPP and is supported by a similar finding in a recent rat study . Studies focused on adult shoulder pathology have frequently evaluated both glenoid version and inclination . One of the key findings of these studies is that superior glenoid inclination increases the risk of superior humeral head translation .…”
Section: Discussionmentioning
confidence: 56%
“…20 Studies focused on adult shoulder pathology have frequently evaluated both glenoid version and inclination. [29][30][31][32][33][34] One of the key findings of these studies is that superior glenoid inclination increases the risk of superior humeral head translation. 29,35 This mirrors the findings of the current study, where humeral head inferior translation was shown to be correlated to inferior glenoid inclination.…”
Section: Discussionmentioning
confidence: 99%
“…Glenoid inclination was defined by the angle formed by the intersection of the transverse axis of the scapula and the plane perpendicular to the face of the glenoid fossa. 10,[16][17][18] Prosthesis inclination was defined as the angle formed between the transverse axis of the scapula and the glenoid baseplate. These measurements are automated in the Glenosys software.…”
Section: Methodsmentioning
confidence: 99%
“…• Use the premorbid glenoid morphology as a patient-specific guide for the selection of the implant and its placement, to reconstruct normal glenoid version and inclination, and to restore the normal premorbid joint line position. Most patients have native glenoid version between 6°and 8°of retroversion 22 . Correcting version to neutral for all patients would lead to overcorrection of pathologic version and unnecessary removal of bone, particularly of the anterior subchondral bone.…”
Section: Contraindicationsmentioning
confidence: 99%